Study of transient response of DC motor using Matlab/Simulink / Norhaida Md Zin - Md Zin, Norhaida (2010)
This thesis discussed the 'Study of State Response of DC Motor using MATLAB/ SIMULINK'. It consists of the open loop system and close loop system. The speed control method of the DC Motor is investigated through open loop system by changing the namely field resistance, armature voltage and armature resistance. The close loop system or feedback system is investigated by using the PI controller and Fuzzy controller.